(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aimed to identify the relationship between psychological flow, optimism, and the level of ambition among faculty members at Prince Sattam bin Abdulaziz University Al-Kharj, Saudi Arabia. The study sample consisted of (150) faculty members from different colleges of the university, who were chosen randomly. The research tools included a scale (psychological flow, optimism scale, and level of ambition), which the researchers prepared. After confirming the psychometric characteristics, the application was applied to the research sample. The research had used the quantitative descriptive method. The results found a positive correlational relationship between (0.01) between psychological flow, optimism, and the level of ambition in favor of assistant professors. Furthermore, the research found statistically significant differences on the scale of the ambition level according to the different research variables in experience and nationality. There were no statistically significant differences between the mean scores of faculty members on the psychological flow scale (career title, gender). The constant variable was statistically significant, and the psychological flow cannot be predicted. The research had recommended conducting studies that measure psychological flow according to other variables of the research sample..